Financial Inclusion Through Digital Banking: Bridging the Gap for Underserved Communities - Rotinsulu, Clara Neltje Meini; Murniati, Sitti; Herlina, H (SAFE-Network, 2025)
This study presents a systematic literature review examining the role of digital banking in advancing financial inclusion among underserved communities. Drawing upon 81 peer-reviewed articles published between 2015 and 2024, the research explores how mobile banking, fintech platforms, and agent-based banking models contribute to overcoming traditional barriers to financial access. The review identifies critical enablers such as digital infrastructure, regulatory innovation, financial literacy, and inclusive technology design. It also uncovers persistent challenges including the digital gender divide, lack of digital trust, and socio-economic disparities. Cross-regional analysis reveals that countries with integrated strategies—combining digital financial services with education, policy coherence, and user-focused design—achieve more equitable outcomes. The study concludes that while digital banking offers substantial promise, its success in promoting financial inclusion requires a supportive ecosystem and inclusive implementation tailored to local contexts.